2013
DOI: 10.3109/14767058.2013.818118
|View full text |Cite
|
Sign up to set email alerts
|

Planned conservative management of placenta accreta – experience of a regional general hospital

Abstract: Successful planned conservative management of placenta accreta is feasible in the setting of district general hospital with facilities for interventional radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This created a heavy burden on the public obstetric services and increased the risk of adverse pregnancy outcomes. [9][10][11][12] Case Comments…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This created a heavy burden on the public obstetric services and increased the risk of adverse pregnancy outcomes. [9][10][11][12] Case Comments…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing evidence on leaving placental tissue behind for conservative management. According to our unit's experience published recently as a case series, 9 planned conservative management of placenta accreta is feasible with good outcome. Prerequisite of success includes careful preoperative planning, involvement of experienced personnel from different disciplines, and a highly dedicated team for postpartum follow-up.…”
Section: Major Placenta Praevia/accreta-compromised Carementioning
confidence: 99%
“…Indeed, false positive results can occur in 18 -28%. 8,22,23) Moreover, if placenta accreta is successfully managed conservatively, the patient remains hemodynamically stable because of a remarkable reduction in blood loss. Therefore, in our institution, cesarean section is currently performed under spinal anesthesia, and is converted to general anesthesia, if necessary.…”
Section: Anesthetic Techniquementioning
confidence: 99%
“…Prophylactic embolization and placement of balloon occlusion catheter Amsalem et al 29) and Lo et al 22) reported that the mean blood loss was 900-1,600 ml in planned conservative management with adjuvant prophylactic uterine artery embolization shortly after cesarean section and that no peripartum hysterectomy was needed in either series. In contrast, Soyer et al 30) performed pelvic embolization in emergency cases alone.…”
Section: Controversial Issuesmentioning
confidence: 99%
“…We reported recently one of the largest case series of placenta accreta that were managed successfully by planned placental conservation 1 . All were typical cases with placenta previa and a history of Cesarean delivery.…”
mentioning
confidence: 99%